Optimal Placement of TCSC Based on Sensitivity Analysis for Congestion Management - Naga Raja Kumari.CH; K. Chendra Sekhar (Institute of Advanced Engineering and Science, 2016)
In a deregulated electricity market whenever congestion management problem occurs, the network collapse because of voltage instability. In this paper total real and reactive power loss deviation based sensitivity indexes (PLDS and QLDS) with rank co-relation concept, has been proposed for the optimal location and operating range of TCSC device. With this placement the power flow in over loaded overhead lines has been reduced and that results in an increased loadability of the power system and also improves the voltage stability and security and also solves the congestion management problem. So ultimately, a more energy efficient transmission system is possible. The case studies were conducted on IEEE 14 bus test system. The ensue corroborate the intended approach for social welfare maximization inreal time.